Determination of α-ketoglutaric and pyruvic acids in urine as potential biomarkers for diabetic II and liver cancer. (April 2015) - Makahleh, Ahmad; Ben-Hander, Gazala Mohamed; Saad, Bahruddin
Background: A simple and sensitive hollow fiber-liquid phase microextraction with in situ derivatization method was developed for the determination of α-ketoglutaric (α-KG) and pyruvic acids (PA) in small-volume urine samples. 2, 4, 6-trichloro phenyl hydrazine was used as derivatization agent.Results: Under the optimum extraction conditions, enrichment factors of 742 and 400 for α-KG and PA, respectively, were achieved. Calibration curves were linear over the range 1 to 1000 ng/ml (r 2 ≥ 0.998). Detection and quantitation limits were 0.03 and 0.02, and 0.10 and 0.05 ng/ml for α-KG and PA, respectively.Conclusion: The concentrations in diabetic II and liver cancer samples were significantly lower than those from healthy people, showing their potential as biomarkers for these diseases.